Legal Issues of Online Reputation Portability in the Digital Economy - Sih Yuliana Wahyuningtyas (Universitas Katolik Indonesia Atma Jaya, 2023)
Reputation influences the level of trust and expectation of others either in social or business interactions. It becomes more important in the digital society, where interactions are often faceless and intangible. However, online reputation systems are usually built within a certain environment, thus locally, and cannot be used beyond that particular environment. A question arises whether such a local online reputation system could lead to lock-in problems that adversely affect competition. This paper begins the analysis by examining the legal aspects of user review as a set of information provided by a reviewer and the reputation as information about the reviewee provided to (other) users. To analyze the legal aspects of online reputation portability, the paper discusses three key issues: first, the legal status of user reviews and addresses the issues of online reputation portability, as recognized under the new Indonesian Data Protection Act, Law No. 27 of 2022, in comparison to the EU General Data Protection Regulation (GDPR), Regulation (EU) 2016/679. Second, it explores whether the limitation of the use of online reputation leads to lock-in problems that might justify the intervention of competition law. Third, it examines online reputation as a reviewee’s asset and the impact of its limitation of use to competition in the viewpoint of Indonesian competition law under Law No. 5 of 1999 compared to EU competition law under Article 102 TFEU.